2014
DOI: 10.1186/1472-684x-13-52
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of patients, family and professional caregivers with Integrated Palliative Care in Europe: protocol for an international, multicenter, prospective, mixed method study

Abstract: BackgroundThe number of people living with advanced cancer and chronic disease has increased worldwide. Many of these patients could benefit from palliative care, focusing on optimising the quality of life of patients and their families facing problems resulting from life-threatening diseases. However, fragmentation and discontinuity of palliative care services often result in suboptimal palliative care. In order to overcome these problems, models using an integrated care approach are increasingly advocated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 39 publications
0
57
0
5
Order By: Relevance
“…Using a multiple embedded case study design [3233], data are being collected from fourteen established integrated care initiatives for older people in seven European countries; Austria, Estonia, Germany, Norway, Spain, the Netherlands and the United Kingdom. The initiatives were already operating within their local health and social care systems.…”
Section: Methodsmentioning
confidence: 99%
“…Using a multiple embedded case study design [3233], data are being collected from fourteen established integrated care initiatives for older people in seven European countries; Austria, Estonia, Germany, Norway, Spain, the Netherlands and the United Kingdom. The initiatives were already operating within their local health and social care systems.…”
Section: Methodsmentioning
confidence: 99%
“…This method is regarded as appropriate for palliative care contexts [12, 13]. A full account of the InSuP-C methodology is published [9]. …”
Section: Methodsmentioning
confidence: 99%
“…The Integrated Palliative Care in cancer and chronic conditions (InSup-C) study that started in 2012, aimed to investigate promising practices in Europe and to formulate requirements for effective palliative care integration across the continent [9]. Within the InSup-C project, the following working definition for integrated palliative care was empirically developed: ‘Integrated palliative care involves bringing together administrative, organizational, clinical and service aspects in order to realize continuity of care between all actors involved in the care network of patients receiving palliative care.…”
Section: Introductionmentioning
confidence: 99%
“…It focused on optimizing the quality of life of patients and their families who were facing problems associated with life-threatening illnesses through the prevention and relief of suffering by early identification and an impeccable assessment and treatment of pain and other physical, psychosocial, and spiritual problems [2]. More recent research has found that palliative care improved relationships, stabilized emotional attitudes toward death, increased the rate of preference for dying at home, as well as contributed to improvements in the quality of care and the quality of life and death of severely ill patients and their relatives [3][4][5].…”
Section: Introductionmentioning
confidence: 99%